Effect of quenching and partitioning on the microstructure evolution and electrochemical properties of a martensitic stainless steel. (February 2016) - Lu, Si-Yuan; Yao, Ke-Fu; Chen, Yun-Bo; Wang, Miao-Hui; Chen, Na; Ge, Xue-Yuan
Highlights: Influence of quenching and partitioning process on stainless steel was studied. Pitting potentials of experimental steel partitioned at 350 and 450 °C were higher. Retained austenite and M3 C carbides existed in matrix of experimental steel. Retained austenite is beneficial for the corrosion resistance of stainless steel. Abstract: A 0.3C–13Cr martensitic stainless steel (MSS) was subjected to quenching and partitioning (Q&P) treatment. Due to the different thermodynamic condition from the standard constrained carbon equilibrium (CCE), both the carbides precipitation and the interface migration occur during the partitioning step in the Q&P treatment. However, a sufficient amount of austenite is still retained in the Q&P treated MSS. After being partitioned at 350 °C and 450 °C, the Q&P treated MSS exhibits better corrosion resistance than the same steel treated via conventional quenching and tempering (Q–T) treatment.